Comparative analysis of elections in the system of local self-government (on the example of Kazakhstan and Turkey) - Bolysbek, М.Ә.; Byulegenova, Б.Б.; Jusupkaliev, А.Ә. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2024)
Еlections in the system of Local Self-Government are a decisive factor, significantly contributing to the democratic process and effective local management. It can be seen that the ways of organizing local elections in Kazakhstan and Turkey, which differ in history, politics and culture, are also different. The purpose of the study of this article is to determine the most effective method of electoral differences and similarities in the system of Local Self-Government of Kazakhstan and Turkey by conducting a comparative analysis, to analyze the impact of these processes on the development of civil society and democracy. The reforms of the local self-government system in Kazakhstan are aimed at spreading the centralization of power and increasing the level of participation of the population in the local political process. An important step in democratic changes in the country is the election of mayors of rural districts by choice of the population over the years, or the use of direct electoral practice. Since the 60s of the XX century, the local electoral system of Turkey has been stable. It is the main developing factor of local government using majority and proportional representation systems. The article presents various aspects of electoral systems, the role of political parties, the level of citizen participation, as well as a comparative analysis to identify problems and difficulties.